PENGARUH LEVERAGE, SIZE, AGRESIVITAS PAJAK DAN PROFITABILITAS TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Murija, 14.05.52.0120; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
Social responsibility has an important role because as a concrete form of the implementation of corporate obligations on the social environment. So that the central government and companies are expected to cooperate in building and welfare environment. This study aims to examine and analyze the effect of Leverage, Size, Tax aggressiveness, and Profitability on Social Responsibility Disclosure on Manufacturing Companies listed on the Indonesia Stock Exchange in the Year 2014- 2016. The sample in this study uses 141 data from 47 manufacturing sector companies listed on the Indonesia Stock Exchange in the period 2014 until 2016. The analysis tools used are descriptive statistical analysis, normality test, classical assumption test, model testing, and hypothesis testing. Based on the research that has been done, found that Leverage has a significant negative effect on Corporate Social Responsibility Disclosure, Corporate Size has a significant positive effect on Corporate Social Responsibility Disclosure, tax aggressiveness has no significant positive effect on Corporate Social Responsibility, Profitability has a significant positive effect on Disclosure of Corporate Social Responsibility.Keywords: Corporate Social Responsibility, CSRD, Leverage, Size, Tax Aggressiveness, Profitability